Hydrological characterization of hydropeaks in mountain rivers (examples from Southern Pyrenees). (23rd September 2022) - Tena, Alvaro; Ville, Fanny; Reñe, Armengol; Yarnell, Sarah M.; Batalla, Ramon J.; Vericat, Damián
Abstract: Streamflow in the Ésera and Upper Cinca Rivers (South Central Pyrenees) experiences alterations in the form of rapid pulses, commonly referred to as hydropeaks, associated with highly variable on‐demand hydropower production from flowing or stored water. A hydrological characterization of the hydropeaks in these two rivers was carried out to examine their distinct hydropeaking pattern during hydrologically contrasted years. The Ésera demonstrated a hydropeaking regime characterized by a high frequency and magnitude, while the Upper Cinca presented a regime with higher frequency but of lesser magnitude. Additionally, this study classified hydropeaks following the shapes proposed in previous studies and assessed their temporal distribution (frequency), timing, and magnitude. Results indicated that hydropeaks were different in shape and magnitude in both rivers; a Front Step pulse shape dominated in the Ésera whereas a Rectangle pulse shape was the most frequent in the Cinca. The Front Step shape had the highest ramping rates during the rising limb of the hydrograph and the shortest time to the maximum flow; whereas the Rectangle shape had higher duration and a larger volume of water released. Hydropeaks in the Ésera were less frequent (one per day) than in the Cinca (two per day). The river Ésera presented, in general, high‐magnitude hydropeaks, with double volume and duration, and three times larger up‐ramping rates and time between flow pulses. Overall, hydropeak shapes in the Ésera varied depending on the hydrological year and the season, while in the Cinca, shape distribution followed the same temporal pattern regardless of year and season; thus, hydropeaking in the Ésera appeared to be much more dependent on the annual hydrology (whether the year is wet or dry ) than in the Cinca. Hydropeaking regimes were characterized based on three categories of variables: magnitude (flow‐based or hydrological variables), timing (duration), and frequency (occurrence). According to the variability of these variables, a total of three statistically significant groups were obtained in the Ésera, while two groups were identified in the Cinca. Hydropeaks can be statistically classified by their hydrological characteristics that in turn may have a direct effect on sediment entrainment and transport with implications to the ecological functioning of rivers. The different shape of the hydropeaks, however, will control the attenuation of the flows downstream and, consequently, the maintenance of the river's competence and capacity. This methodology provides a useful quantification of hydropeaking regimes to assess the potential impacts on physical and biological aspects of river systems.